2018
DOI: 10.1080/10717544.2018.1507058
|View full text |Cite
|
Sign up to set email alerts
|

A local drug delivery system based on visible light-cured glycol chitosan and doxorubicin⋅hydrochloride for thyroid cancer treatment in vitro and in vivo

Abstract: Systemic drug delivery systems (SDDSs) for thyroid cancer treatment are associated with serious side effects including nausea, anorexia, and hair loss as a result of damage to normal tissues. In this study, we investigated the feasibility of a local DDS (LDDS) based on visible light-cured glycol chitosan (GC) hydrogel and doxorubicin⋅hydrochloride (DOX⋅HCl), called GC10/DOX, on thyroid cancer treatment in vivo. Visible light irradiation increased the storage modulus and swelling ratio of the GC10/DOX hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…Among hydrogel systems, an injectable hydrogel is valuable, both because it can directly deliver anticancer drugs near cancer tissues by local injection and because it has a potential for drug loading in the matrices. In our previous studies, the visible light-cured GC hydrogel system was found to be a potent local drug-delivery carrier because of its injectability and the fact that it allows anticancer drugs to be controllably released in a sustained manner [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among hydrogel systems, an injectable hydrogel is valuable, both because it can directly deliver anticancer drugs near cancer tissues by local injection and because it has a potential for drug loading in the matrices. In our previous studies, the visible light-cured GC hydrogel system was found to be a potent local drug-delivery carrier because of its injectability and the fact that it allows anticancer drugs to be controllably released in a sustained manner [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the GC hydrogel has porous structure together with interconnectivity [10][11][12]. These structural properties resulted in in vivo anticancer effects against solid cancers when the GC hydrogel was used as the local anticancer drug-delivery system [10][11][12]. Therefore, it is assumed that GDHCP has a superior anticancer effect against osteosarcoma in vitro and in vivo (Figures 3-8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations